Review of Christopher Clark’s Οι Υπνοβάτες: Πώς η Ευρώπη πήγε στον πόλεμο το 1914 [The Sleepwalkers: How Europe went to War in 1914] - Lemonidou, Elli (Historein, 2015)
There is hardly an issue in the entire history of the 20th century that has caught so much the interest of the historians and has seen the production of such a huge number of books and articles as the one regarding the origins of the First World War. It is no surprise that the explosion of interest in the First World War on the occasion of the centenary year was marked, among else, by new discussions and many publications on this subject. The book that has caught mostly the attention of public and academic debate is no other than Sleepwalkers by Christopher Clark, Professor of Modern History at the University of Cambridge. Through an exhaustive study of the main actors and the motives behind their decisions, characterized by thorough knowledge of the subject and a thrilling narrative style, the author tries to answer the crucial question of how Europe went to war in 1914.